2020
DOI: 10.3892/ol.2020.11453
|View full text |Cite
|
Sign up to set email alerts
|

High SPRR1A expression is associated with poor survival in patients with colon cancer

Abstract: High expression of small proline-rich protein 1A (SPRR1A) has been shown to be associated with tumor prognosis; however, the association between SPRR1A expression and colon cancer prognosis remains unclear. The present study sought to evaluate the association between SPRR1A expression and the clinicopathological characteristics of colon cancer, and to examine its potential prognostic value. A total of 114 patients with colon cancer were included. SPRR1A expression was evaluated by immunohistochemical staining,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…In the current study, we also demonstrate that LV SPRR1A was upregulated in patients with HFrEF ( Figure 5C ), which is consistent with reports in mice with ISO-induced myocardial injury ( 30 ) and renal I/R injury ( 31 ). Interestingly, SPRR1A expression was also reported to be inversely linked with survival of cancer patients ( 37 39 ). Here, we also show that Sprr1a was downregulated in hearts and CMs by Carv ( Supplemental Figure 10 ), concurrent with upregulation of miR-150 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we also demonstrate that LV SPRR1A was upregulated in patients with HFrEF ( Figure 5C ), which is consistent with reports in mice with ISO-induced myocardial injury ( 30 ) and renal I/R injury ( 31 ). Interestingly, SPRR1A expression was also reported to be inversely linked with survival of cancer patients ( 37 39 ). Here, we also show that Sprr1a was downregulated in hearts and CMs by Carv ( Supplemental Figure 10 ), concurrent with upregulation of miR-150 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Squamous differentiation, unlike the adenocarcinoma component, essentially expresses SPRR1A , as described above. After verifying that the expression of keratin 5 (KRT5) did not correlate with that of SPRR1A ( S3B Fig ), we used the same method as in S1C and S1D Fig to exclude the eight patients with high transcript levels of KRT5 , a squamous epithelial marker [ 19 ], above the average plus two s.d. ( S3C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that SPRR3 promoted the proliferation of breast cancer and colorectal cancer cells via the AKT and mitogen-activated protein kinase (MAPK) pathways [ 16 , 17 ] and that SPRR2B facilitated the growth of gastric cancer via the MDM2-p53/p21 signaling pathway [ 18 ], suggesting that SPRR family genes may be involved in cancer growth signaling. Furthermore, recent studies have reported the prognostic value of a high expression of SPRR1A in colon cancer, breast cancer and diffuse large B-cell lymphoma [ 19 21 ]. We have also found that SPRR1A may be associated with the characteristics of cancer stem cells derived from osteosarcoma [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…(C and D) Tumor volumes were measured every five days and calculated as described in the Method section, which revealed that SPRR2B-shRNA significantly attenuated tumor growth while overexpressing SPRR2B exerted opposite effects. malignancy progression, such as SPRR1A, [25][26][27][28] SPRR1B, [29][30][31] SPRR2A, [32][33][34][35] and SPRR3. [36][37][38][39] However, SPRRs can serve as either tumor suppressors 39 or oncoproteins 38 in different malignancies.…”
Section: Discussionmentioning
confidence: 99%